Improving Innovation And Differentiation At PT. Ayo Menebar Kebaikan In Developing New Quality Products - Nashrul hafidz; Anas Hidayat (Citakonsultindo, 2024)
This research aims to determine strategies for increasing innovation and product differentiation at PT. Ayo Menebar Kebaikan. A company operating in the chemical sector as well as raw materials for soap and perfume, in an effort to increase competitiveness in the market, and in facing challenges to create products that are innovative and different from competitors. This research uses a qualitative approach with information collection methods obtained through in-depth interviews with management and employees as well as analysis of company documents. The research results show that the combination of a strong innovation culture, collaboration between departments, and a consumer needs-oriented approach plays a key role in the success of new product development. This study provides insight into the importance of innovation and differentiation strategies in strengthening a company's position in the market and suggests practical steps that can be implemented by other companies wishing to achieve similar goals.